Political Humor in Abdur Arsyad's Stand-up Comedy - Prahastiwi, Adventyna (Universitas Dian Nuswantoro, 2022)
The study aimed to identify types of political humor in Abdur Arsyad’s stand-up comedy by applying the Script-Based Semantic Theory of Humor (SSTH) and describing the language games to support humor. This research is a qualitative descriptive study. The data consisted of Abdur Arsyad’s stand-up comedy video published on Youtube. The data method collection used listening and note-taking techniques. The result showed that political humor in Abdur Arsyad’s stand-up comedy can be classified into (1) humor to criticize political figures and political groups, and (2) humor that describes bad conditions in society: political repression, education, corruption, and social inequality. Two language games are used, namely sound games and meaning games.